KOMUNITAS NEMATODA TANAH DI BLOK LINDUNG HUTAN PENDIDIKAN KONSERVASI TERPADU TAMAN HUTAN RAYA WAN ABDUL RACHMAN - Yoshua Gdemakarti; Bainah Sari Dewi; I Gede Swibawa; Irwan Sukri Banuwa (Lambung Mangkurat University-Indonesia, 2021)
Hutan Pendidikan Konservasi Terpadu (HPKT) is part of Taman Hutan Raya Wan Abdul Rachman (Tahura WAR) enabled to support educational activities and research. The quality of the soil in this area is influenced by several factors, one of the factors i.e. nematodes. The aim of study to know the community of nematodes on the Protection Block, Hutan Pendidikan Konservasi Terpadu, Wan Abdul Rachman Forest Park. The research was conducted in April to May 2018. The soil samples were taken on arboretum seven, arboretum eight, arboretum nine and arboretum 10. Nematode observations were conducted in the laboratory of Plant Pests, Faculty of Agriculture, University of Lampung. Nematodes have been identified to genus level based on morphological traits. The result of study showed that there are 29 genus of nematode consists of 17 plant parasitic nematode genera, seven nematoda bacterial-feeding, three nematode fungal-feeding, one omnivore nematode and one predator nematode. The dominant nematode genera are Criconomella, Helycotylenchulus dan Rotylenchulus. The abundance of nematodes ranges from 251-613 individuals / 300cc soil. The diversity of soil nematodes based on the Shannon-Wienner index ranges from 2.33-2.62. The Shannon-Whienner Index criteria are classified as moderate. The Simpson Index ranges from 0.862-0.907. The highest similarity index genus in arboretum seven with arboretum nine and arboretum eight with arboretum nine with a value of 0.81. The lowest in arboretum seven and arboretum 10 that is 0.63.